Recent Progress in SiC Nanostructures as Anode Materials for Lithium- Ion Batteries - Fan, Xiaohong; Deng, Dingrong; Li, Yi; Wu, Qi-Hui (Current Materials Science, 2023)
Large volume variation during charge/discharge of silicon (Si) nanostructures applied as the anode electrodes for high energy lithium-ion batteries (LIBs) has been considered the most critical problem, inhibiting their commercial applications. Searching for alternative highperformance anodes for LIBs has been emphasized. Silicon carbide (SiC) nanomaterials, a wide bandgap semiconductor with excellent mechanical properties, have been investigated as anode electrode materials even as active materials, protective layers, or inactive buffer stuff. In this minireview, we briefly summarize the synthesis of SiC nanostructures, the application of SiC/C anode materials, and SiC/Si composite anodes in LIBs.
Keywords: anode